Nigeria and West Africa’s Silk Road: The New Crescent Economy - Gamawa, Yusuf Ibrahim (American Economic & Social Review, 2019)
The ancient city of Kano that is now located in north western Nigeria was an important player in the Trans-Saharan trade that flourished before the advent of the Europeans. The Trans- Sahara trade also predates the Danfodio Jihad that established the Caliphate system across northern Nigeria. The trade was seen to have involved many of the Sahel states in present times, but most importantly cities that distinguished themselves in the production of various commodities like Timbuktu, Gao, Djenne and Sijilmasa in Morocco. Since the demise of such trade, many cities that have hitherto been part of it, have lost relevance in the economic affairs and have been struggling to create new economies and have not been able to do so in modern times. Kano had been the economic base of northern Nigeria and its economy had supported the entire north of Nigeria as a result of the Trans-Sahara trade. Kano became known for trade across the Sahel and the Sahara for its textile and other services that include dyeing of clothing that were sent to as far as Morocco. The paper takes a look at the ancient Sahel economy and Kano’s involvement and insists that for the economy of Northern Nigeria and that of Kano to be revamped, a new strategy will have to be developed. This strategy will look at reviving the ancient trade links that existed before and make for the construction of infrastructure, industries and necessary tourism potentials available. And that it is only by doing so that Kano as city will take its proper place among cities like Timbuktu and Gao, and impact on the economy of Northern Nigeria and by extension the Nigerian nation.